Self-Efficacy in Elementary School Digital Competence: A Bibliometric Analysis of 21st Century Learning Research - Putri, Irni Rachmawati; Ratri, Safitri Yosita; Kawuryan, Sekar Purbarini (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
This study aims to analyze bibliometric mapping of research on self-efficacy and digital competence in Scopus-indexed journals published between 2015 and 2025. The dataset was retrieved from the Scopus database in March 2025 using the query “keywords” with a filter for elementary school, covering a time span of 2015–2025. After screening, a total of 127 documents were included. Bibliometric data were processed using Microsoft Excel and VOS Viewer version 1.6.20 with parameters set at a minimum of five keyword occurrences and full counting method. The annual distribution of publications shows an increasing trend in recent years, reflecting growing academic attention to the topic. Analysis by country indicates that Spain and Germany are the most productive contributors, with active collaboration networks identified at regional and institutional levels. Co-authorship analysis confirms the presence of collaborative research, though large-scale international collaboration remains limited. Document type analysis shows that most outputs are journal articles, followed by conference papers. Keyword co-occurrence mapping highlights “self-efficacy,” “human,” and “digital competence” as the most frequently used terms. Less explored but emerging themes include “digital technology,” “human experimental,” and “questionnaire,” suggesting potential research gaps. Overall, the findings indicate that while research on self-efficacy in students’ digital competence is expanding, opportunities remain for broader international collaboration and exploration of underrepresented themes in 21st century educational practices.